Report of Planning Commission Working Group on Electronics Industry Plan For 1978-83 - Planning Commission (Planning Commission, 1978)
To suggest the optimal way of achieving the desired objectives in terms of size of units, organised sector versus decentralised sector, expansion/diversification/modernisation/rationalisation of existing units with due regard to technological/production cost and employment consideration.
Department of Electronics
Department of Electronics